Atypical Rosai-Dorfman Disease with Lacrimal Gland Involvement. (July 2013) - Hsu, Hung-Yuan; Chen, Zoe Tzu-Yi; Tsai, Ching-Yao; Liou, Shiow-Wen; Woung, Lin-Chung
Abstract Purpose: Rosai-Dorfman disease is a rare, benign, idiopathic histocytic proliferative disorder that typically presents in young adults with painless cervical lymphadenopathy. Here we report an atypical case of Rosai-Dorfman disease involving orbit tissue and lacrimal gland, unilaterally. Case: A 69-year-old Asian women developed a painless palpable mass with local edema over the left upper eyelid over several months. Computed tomography (CT) showed an orbital mass with homogenous soft tissue density over the left lacrimal gland and superior orbital area. The patient underwent complete excision of the orbital tumor. Observations: The histopathology revealed diffuse and nodular infiltrations of S-100 positive histiocytes, plasma cells and lymphocytes. Emperipolesis (lymphocytophagocytosis) was also noted. These findings were consistent with Rosai-Dorfman disease. Chest CT revealed hilar lymphadenopathy. Three months after excision of the orbital mass, the patient developed lymphadenopathy in the extremities that resolved spontaneously over a few weeks. There were no complications or recurrence without systemic treatment after the complete excision. Conclusions: Orbital Rosai-Dorfman disease is a rare disorder, especially in Asia. Though there is no consensus on therapeutic choices, including corticosteroids, chemotherapy, radiation therapy, and surgical excision, the complete surgical excision performed in this case was without complication and had a favorable outcome.